Data detection based iterative channel estimation for coded SM-OFDM systems - Leblebici, Mehmet Merih; Doğan, Hakan; Panayırcı, Erdal; ACAR, YUSUF (IEEE, 345 E 47Th St, New York, Ny 10017 USA, 2016)
The combination of spatial modulation (SM) and orthogonal frequency division multiplexing (OFDM) as SM-OFDM is a recently proposed efficient modulation scheme with exploiting the index of transmit antenna to convey information bits for multiple-input multiple-output (MIMO) wireless communication systems due to its low complexity feature. The pioneering works assume that the perfect channel state information (P-CSI) or pilot symbols aided channel estimation (PSA-CE) is available at the receiver. The open question is whether the accuracy of pilot based channel estimation is satisfactory to accomplish high data rate transmission in SM-OFDM systems. This paper explores the iterative channel estimation (ICE) problem for the coded SM-OFDM systems. We showed that the quality of the channel estimation can be further enhanced by the detection of symbols at the receiver. Through comparative simulations, we show that the proposed ICE method has notable bit error rate (BER) performance compared with the PSA-CE method for the binary phase shift keying (BPSK) modulation over the typical urban (TU) channel model.
Keywords: MIMO; spatial modulation; OFDM; iterative channel estimation; interpolation